2013
DOI: 10.1111/hsc.12071
|View full text |Cite
|
Sign up to set email alerts
|

Informal caregivers' participation when older adults in Norway are discharged from the hospital

Abstract: This paper describes the participation of informal caregivers in the discharge process when patients aged 80 and over who were admitted from home to different hospitals in Norway were discharged to long‐term community care. Data for this cross‐sectional survey were collected through telephone interviews with a consecutive sample of 262 caregivers recruited between October 2007 and May 2009. The Discharge of Elderly Questionnaire was developed by the research team and was designed to elicit data concerning info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 30 publications
5
32
0
1
Order By: Relevance
“…Spouses also had less desire to seek health-related information compared with the patients' children . That spouses feel less informed than adult children during the discharge process has also been found in another Nordic study (Bragstad et al 2014). In the Nordic countries, family members had more unfulfilled knowledge expectations and less access to knowledge from healthcare providers compared with family members from the southern European countries .…”
Section: Quality Of Recoverysupporting
confidence: 61%
“…Spouses also had less desire to seek health-related information compared with the patients' children . That spouses feel less informed than adult children during the discharge process has also been found in another Nordic study (Bragstad et al 2014). In the Nordic countries, family members had more unfulfilled knowledge expectations and less access to knowledge from healthcare providers compared with family members from the southern European countries .…”
Section: Quality Of Recoverysupporting
confidence: 61%
“…Data were collected in structured self-report (face-to-face [patients] and telephone [informal caregivers]) interviews. The results from Phase One of the main study have been reported elsewhere [53,55,56]. …”
Section: Methodsmentioning
confidence: 99%
“…In the hospital setting, informal caregivers struggle to be more involved [52]; however, participation can be hampered by a lack of dialogue between formal and informal caregivers [52,53]. Furthermore, research has shown that informal caregivers can act as a “bridge” between the patient and formal care, facilitating formal care [54] by initiating the process of acquiring formal help for their home-bound older relatives [37].…”
Section: Introductionmentioning
confidence: 99%
“…Å informere pårørende om pasientens helsetilstand og behandling er avhengig av pasientens samtykke, så sant situasjonen tilsier det (28). Hvordan taushetsplikten blir tolket og praktisert av helsepersonell kan vaere en faktor som påvirker pårø- (11,32,33). Det er tydelig at det må arbeides med hvordan pårørendeinvolvering kan bli en eksplisitt og integrert del i helsepersonells yrkesutø-velse.…”
Section: Diskusjonunclassified